Realizing the interaction mechanism of the solute grain boundary segregation and precipitation behavior of Mg-Zn-Gd-Sm alloy - Yang Zhou; Hansong Xue; Shanyi Lan; Jinyu Zhang; Jia She; Dingfei Zhang; Jia Hu; Fusheng Pan (Materials Research Letters)
A novel Mg-6.2Gd-4.2Sm-1.2Zn alloy with a superior strength-ductility combination was achieved by traditional extrusion process and aging. Based on the characteristics of substitutional solution among rare earth (RE) elements, the Sm substitute part Gd element change the morphology of the LPSO phase, and the volume fraction of the 14H-LPSO phase increases, leading to a finer size and more dispersed distribution. Meanwhile, the Sm addition reduces the level of GB segregation of Zn and Gd, which further affects the precipitation of nano-precipitates during aging. The results offer insight into determining the precipitation behavior of second phases via regulating solute GB segregation.